Variations in Energy Metabolism Precede Alterations in Cardiac Structure and Function in Hypertrophic Preconditioning - Wu, Jian; Lu, Jing; Huang, Jiayuan; You, Jieyun; Ding, Zhiwen; Ma, Leilei; Dai, Fangjie; Xu, Ran; Li, Xuan; Yin, Peipei; Zhao, Gang; Wang, Shijun; et al. (Frontiers in Cardiovascular Medicine, 2020)
Recent studies have unveiled that myocardial hypertrophic preconditioning (HP), which is produced by de-banding (De-TAC) of short-term transverse aortic constriction (TAC), renders the heart resistant to hypertrophic responses induced by subsequent re-constriction (Re-TAC) in mice. Although cardiac substrate metabolism is impaired in heart failure, it remains unclear about the role of HP-driven energetics in the development of cardiac hypertrophy. Here, we investigated energy metabolism, cardiac hypertrophy and function following variational loading conditions as well as determined the relationships of these changes in HP. Male C57BL/6J mice (10-12 weeks old) were randomly subjected to sham operation (Sham), 3 days of TAC (TAC 3d), 4 days of De-TAC (De-TAC 4d), 4 weeks of Re-TAC (Re-TAC 4W), or 4 weeks of TAC alone (TAC 4W, without prior aortic banding and de-banding). Cardiac hemodynamics, echocardiography, and histology were evaluated, followed by quantitative PCR for fetal genes (ANP and BNP), glucose metabolism related genes (glut4, pdk4) and fatty acid oxidation related genes (mcad, pgc1α, mcd, pparα) and by western blot for a metabolic stress kinase AMPK and its downstream target ACC. Re-TAC 4W mice showed less impairment in glucose and fatty acid metabolism, as well as less cardiac hypertrophy and dysfunction, compared with TAC 4W mice. Moreover, no significant difference was found in myocardial hypertrophy, fibrosis and cardiac function in TAC 3d or De-TAC 4d, compared with Sham. However, glut4, pdk4, mcad, pgc1α, mcd, pparα were all decreased, while AMPK and ACC were activated in TAC 3d, and returned to Sham level in De-TAC 4d, suggesting that the change in myocardial energy metabolism in HP mice was earlier than that in cardiac structure and function. Collectively, HP improves energy metabolism and delays cardiac remodeling, suggesting that early metabolic improvements may be critical determinants for structural and functional recovery in cardiac hypertrophy.